Impact of Hot Pressing Temperature on Medium Density Fiberboard (MDF) Performance - W. Gul; A. Khan; A. Shakoor (Advances in Materials Science and Engineering)
Hot pressing temperature is determined according to the performance of boards, type of glue, and production efficiency of hot press. During hot pressing, the thermal energy has enhanced the plasticity of the fiber and created conditions for the integration of different bonds. The thermal energy will cause the moisture in raw board to vaporize. Temporary heating will expedite the solidification of hot set resin for decreased friction and increased fluidity. The hot pressing temperature usually refers to the temperature of hot pressing plate, but what plays function in actual use is the temperature inside the raw board. This research investigates the performance of MDF with respect to hot pressing temperature. The strength and water resistance of the product are improved with the increase of hot pressing temperature from 140°C to 160°C, the Modulus of Rupture (MOR) is increased by 9.8%, the Internal Bonding (IB) is increased by 33.6%, the water absorption (Wt) is decreased by 38.2%, and the thickness expansion rate (Ts) is decreased by 15.2%.